Reproducibility of antibacterial effects of ethanol extracts from Piper crocatum Ruiz & Pav., and Piper betle L. (Piperaceae), against common acne, Propionibacterium acnes (Gilchrist, 1900) Douglas & Gunter, 1946 (Propionibacteriaceae) - Reza Anindita; Mita Fatmawati; Maulin Inggraini; Intan Kurnia Putri; Maya Uzia Beandrade (Bioma, 2025)
Red and green betel leaf plants are useful as medicine but need to be tested for antibacterial ability to be used as raw materials for making anti-acne serum. This study aims to determine the antibacterial effect of red and green betel leaves on the sensitivity response of Propionibacterium acnes bacteria. This experimental study used samples of red and green betel leaves with procedures including sample preparation, maceration, qualitative phytochemical screening, and testing of antibacterial compounds in ethanol extracts of 70%, 80%, 90% and 100% samples using the Kirby Baeur method. Positive control was clindamycin 30 µg antibiotic and negative control was sterile distilled water. The yield of thick extracts of red and green betel leaves was 13.5% and 15%. The administration of 70%, 80%, 90%, and 100% thick extract of red betel leaves was able to inhibit Propionibacterium acnes with inhibition zone diameters of 16 mm, 18 mm, 18.5 mm, and 19 mm while green betel was 18 mm, 18 mm, 21 mm, 23 mm. The administration of thick extracts of red and green betel leaves is effective in inhibiting the growth of P. acnes and has the potential to be used as raw material for anti-acne serum formulations.